Endosonographic and manometric assessment of the anal sphincters after ileal pouch-anal anastomosis - Sudoł-Szopińska, Iwona (Radiology and oncology (Ljubljana), 2003)
Background. The aim of this study was to compare endosonography and manometry of the anal sphincters in patients after ileal pouch-anal anastomosis (IPAA). Patients and methods. Ten patients aged between 23 and 50 years with IPAA perforrned for ulcerative colitis were examined with anal endosonography (AES)and manometry. Results. AES visualised abnormal image of the internal anal sphincter (IAS) in 9 patients (90%). Defects of the external anal sphincter (EAS) and puborectalis muscle (PR) were shown in 4 patients (40%). In 5 patients (50%) correlation between endosonographic and manometric assessment for the all analysed muscles: IAS, EAS and PR was found. In 4 cases(40%) both methods correlated with the evaluation of the EAS only and in 2 patient (10%) no correlation was found. Correlation between both methods forthe IAS was found in half of the patients (50%) while in the evaluation of the EAS and PR dynamic activity, it was found in 9 cases (90%). Conclusious. Anal endosonography and manometry allow us to assess fhe morphology as well asthe function of the anal sphincters in patients with IPAA. The methods mentioned above show high correlation in the assessment of the EAS function (9cases; 90%) whereas in the case of IAS, manometry frequently (5 patients; 50%) does not confirm endosonografically detected defects.
Keywords: analni sfinkter; Anastomosis, Surgical; Anastomoza kirurška; Anus; Colitis, Ulcerative; diagnostika; Kolitis ulcerozni; Manometrija; Manometry; Surgery; ulcerozni kolitis; Ultrasonography; ultrazvočna diagnostika